2014
DOI: 10.1148/radiol.13122901
|View full text |Cite
|
Sign up to set email alerts
|

Carpal Tunnel Syndrome: Diagnosis by Means of Median Nerve Elasticity—Improved Diagnostic Accuracy of US with Sonoelastography

Abstract: Sonoelastography provides significant improvement in the diagnostic accuracy of the ultrasonographic assessment of CTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 29 publications
5
80
0
1
Order By: Relevance
“…Orman et al have published that mean tissue strain was lower in the patients with CTS than in the controls similar to our results [22]. Miyamoto et al concluded that elastography provided significant improvement in the diagnostic accuracy of the ultrasonographic assessment of CTS [23]. Ghajarzadeh et al analyzed 60 median nerves by using the blue and red pixels and their indexes in a three-dimensional matrix.…”
Section: Discussionsupporting
confidence: 88%
“…Orman et al have published that mean tissue strain was lower in the patients with CTS than in the controls similar to our results [22]. Miyamoto et al concluded that elastography provided significant improvement in the diagnostic accuracy of the ultrasonographic assessment of CTS [23]. Ghajarzadeh et al analyzed 60 median nerves by using the blue and red pixels and their indexes in a three-dimensional matrix.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have suggested using the CSA difference between a proximal median nerve measurement at the level of the pronator quadratus and a measurement within the carpal tunnel, resulting in a delta CSA (Δ-CSA). Although these two recently proposed parameters (R-CSA, Δ-CSA) demonstrate better discriminating performance than CSA measurement alone, no correlation was found with NCS severity, and threshold values for NCS grades were not defined [17][18][19].…”
Section: Introductionmentioning
confidence: 88%
“…Carpal tunnel syndrome (CTS) is a common median nerve compression neuropathy at the level of wrist (1). It causes numbness and pain in the volar surface of the thumb through the radial half of the ring finger (2).…”
Section: Introductionmentioning
confidence: 99%
“…Several study have attempted to identify the risk factors of carpal tunnel syndrome (1,3,(6)(7)(8)(9). They identified different personal and medical risk factors of CTS such as age, gender, overweight, arthritis, diabetes mellitus, rheumatoid and thyroid disorders (1,3,(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation